KEWENANGAN KEJAKSAAN DALAM MENGAJUKAN PERMOHONAN PEMBATALAN PERKAWINAN (Suatu Penelitian di Kabupaten Aceh Besar) - Mardiyah Mardiyah; Azhari Yahya (Islamic Criminal Law Department, Faculty of Sharia and Law, UIN Ar-Raniry, 2018)
This research aims to know the authority of the public prosecutor in applying the cancellation of marriage application at Mahkamah Syar’iyah Jantho. Article 22 of the Act Number 1, 1974 on Marriage states that a marriage bond might be cancelled if it failed to fulfill the requirement. However, in the practice at the Mahkamah Syariyah Jantho, the prosecutor has never been conducted such authority. This research aims to explore the reasons of the Public Prosecution Office has never been applying for the invalid marriage and legal consequence for the prosecution office when it fails to conduct its duties. This is field research, by using a juridical empirical approach. The research findings are the public prosecution office might apply for r the marriage cancellation towards marriage as ruled in Article 23 point c of the Marriage Act due to reasons for the Prosecution Office that has never been applying is due to the reason that there is no special explanation regarding the matter and there is different perception. The Prosecution Office or the prosecutor but it has implication over the ignorance of not applying the cancellation of marriage. Thus in terms of keeping the law is working, and preventing the offense committed in the future and there is legal certainty amongst people there should be a common goal and aims in imposing law by law enforcers in responding the authority and the position of the public prosecution office in applying the application of marriage cancellation.